The UK and the EU: New opportunities, old obstacles. Prospects for UK-EU cooperation in foreign and security policy after the UK elections - Nicolaicvon Ondarza (Stiftung Wissenschaft und Politik (SWP), 2024)
Labour has won a landslide in the United Kingdom (UK) snap elections and will now lead the government. Following the mutual estrangement caused by Brexit, among other changes, this provides an opportunity to revitalise relations with the European Union (EU). Particularly in foreign, security and defence policy, cooperation has already increased in the wake of Russia's war of aggression, but mainly on an ad hoc basis. In the medium term, it is not a question of reversing Brexit, but rather of establishing an EU-UK Common Strategic Initiative - in other words, a new model for structured relations with a partner that is very important for the EU and Germany. Here, the EU should also show more flexibility than in the past.
Keywords: 320; Vereinigtes Königreich; Europäische Union; Beziehungen zwischen EU und Großbritannien; Außen- und Sicherheitspolitik; britische Unterhauswahl 2024; Gemeinsame Strategische EU-UK-Initiative; Premierminister Rishi Sunak; Keir Starmer; Labour-Partei; United Kingdom (UK); European Union (EU); Northern Ireland; Brexit; EU-UK Common Strategic Initiative; Rishi Sunak; Kier Starmer; Nigel Farage; Conservative Party; elections; Labour; Liberal Democrats; Permanent Structured Cooperation (PESCO)